Usaha Mikro Camilan di Desa Kedungsalam Kecamatan Donomulyo, Kabupaten Malang - Dwi Danesty Deccasari; Didik Priyo (Jurnal ABM Mengabdi, 2015)
Kedungsalam village is one of the villages in Malang, more tepanya close to the famous tourist attraction enough that Ngliyep Beach. This area has a population of nearly 50% are poor and most of the livelihoods of farming on land that rely on rain. The production process of each of the partners are still using very basic equipment so the chances of increasing market is still not fully utilized by micro entrepreneurs. Regional product marketing partners are in schools and stalls as well as hawkers vegetables every day around the community. Increasingly high demand during the holidays and celebrations ceremonies that diselenggerakan Beach Ngliyep currently these attractions continue to reform to attract both domestic and foreign. Patterns applied management is still very simple, there is no detailed records regarding the entry and exit of goods and expenses incurred so that an unknown number of net profits from the crops. IbM program is expected to impact the development of micro-enterprises can create greater employment opportunities that can absorb labor in the village which is an average of the population are living in poverty.